Commercial Diplomacy and Internationalization of SMEs: A Scoping Review - Alsuwaidi, Fatima; Raziq, Muhammad; Batool, Uzma (International Review of Management and Marketing, 2024)
The purpose of this study is to synthesize information about the possible advantages of SME internationalization. The primary question driving this scoping review is: What is the extent to which field of commercial diplomacy has identified its potential to benefit the SMEs, specifically in their internationalization efforts? We do have done a scoping review adhering to a five-step methodology, and extensively reviewing the relevant studies. A systematic literature review was conducted using electronic databases with predefined inclusion-exclusion criteria. 191 articles were screened, yielding 19 relevant studies for final analysis. Our review not only offers a comprehensive analysis of the current research on the relationship between CD and SME internationalization, but also identifies key themes. While doing so, this study sheds light on significant findings, on-going debates, and identifies research gaps that need future exploration. The study’s theoretical and practical implications are also discussed. The role of SMEs in economic growth and innovation is crucial in the context of globalization. Nevertheless, SMEs have several internal and external challenges throughout their process of internationalization. Despite the established significance commercial diplomacy plays in the internationalization efforts of SMEs, centre of attention remains on large organization and their facilitation. While the current body of research mostly focuses on the economic consequences of internationalization for bigger companies, it remains limited on SMEs.